Attrition rate and its predictors among adults receiving anti-retroviral therapy following the implementation of the "Universal Test and Treat strategy" at public health institutions in Northern Ethiopia. A retrospective follow-up study. Issue 11 (November 2022) - Bantie, Berihun; Abate, Moges Wubneh; Nigat, Adane Birhanu; Birlie, Tekalign Amera; Dires, Tadila; Minuye, Tigabu; Kerebeh, Gashaw; Tiruneh, Chalie Marew; Moges, Natnael; Chanie, Ermias Sisay; Feleke, Dejen Getaneh; Mulu, Animut Tilahun; et al.
Abstract: Introduction: Since 2016, the Ethiopian Federal Ministry of Health has adopted a "Universal Test and Treat" strategy to treat human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS). In this test and treat era, access to anti-retroviral therapy (ART) has been rapidly expanded. On the other hand, poor retention of patients on ART remains a serious concern for reaching ART program goals. Thus, this study is targeted at investigating the attrition rate and its predictors among HIV-positive adults following the implementation of the "test and treat" strategy in Ethiopia. Methods: An institution-based retrospective follow-up study was conducted among 1048 HIV-positive adults receiving ART at public health institutions in Bahir Dar city, Northern Ethiopia. Data were extracted from randomly selected patient charts, entered into Epidata 4.6 and exported to Stata 14.2 for analysis. Kaplan-Meier curve was used to estimate individuals' attrition-free probability at each specific point in time. Both bivariable and multivariable cox regression models were fitted, and variables with a P-value of <0.05 in the multivariable model were considered as significant predictors of attrition. Results: A total of 1020 (97.3%) study participants were included in the final analysis. The attrition rate of individuals was 15 per 100 person-years of observation (95% CI: 13.5–16.9 per 100 PYO). World Health organization (WHO) stage III/IV clinical diseases (Adjusted hazard ratio/AHR/1.75 (95% CI:1.24–2.48)), Not disclosing HIV-status (AHR 1.6 (95% CI: 1.24–2.05)), rapid initiation of ART (AHR 2.05 (95%CI:1.56–7.69)), No history of ART regime change (AHR2.03 (95% CI: 1.49–2.76)), "1J (TDF_3TC-DTG)" ART regimen (AHR 0.46 (95%CI: 2.18–3.65)), and Poor ART adherence (AHR2.82 (95%CI: 2.18–3.65)) were identified as significant predictors of attrition rate of HIV positive adults. Conclusion: Following the implementation of the universal test and treat area, the attrition rate of adults living with (HIV) found to be high. Due attention shall be provided to those individuals who didn't disclose their status, were initiated into ART within seven days, had WHO stage III/IV clinical disease, had poor adherence history, had no regimen change, and are not on 1J (TDF_3TC-DTG) ART regimen type. Abstract : Attrition rate; Predictors; Test and treat era; Northern Ethiopia.